KINERJA KEUANGAN SESUDAH DAN SEBELUM SPIN OFF UNIT USAHA SYARIAH KE BANK UMUM SYARIAH - Kuncoro, Amin; Yulianto, Heru (Prodi Ekonomi Syariah Pascasarjana IAIN Kudus, 2018)
This study aims to distinguish between conventional banks and Islamic banks before and after Spin Off. The population and samples are Islamic banks in 2011 - 2013 before spin off and 2013 - 2016 after the spin off totaling 5 banks. The design of this study uses descriptive analytics, with the results of the study there are differences in Islamic banks that do spin offs.